Hypovitaminosis B12 in Pregnant Women Suffering from Gestational Diabetes Mellitus (Medical Forum Monthly, 2020)
Objective: To determine the frequency of vitamin B12 deficiency (hypovitaminosis B12) in Pregnant Women suffering from Gestational Diabetes mellitus,Study Design: Observational / case control studyPlace and Duration of study: This study was conducted at the Department of Pathology and Gynecology/Obstetrics, Indus Medical College, Tando Muhammad Khan from Jan 2018 to September 2019.Materials and Methods: A sample of 200 pregnant women was divided into control normal pregnant women and GDM diagnosed cases. Subjects were selected by non – probability convenient sampling fulfilling criteria. Blood samples were collected by venesection and centrifuged to get sera. Hematological findings, blood glucose, HbA1c and vitamin B12 were estimated. Hypovitaminosis B12 was defined as <300 pg/ml. Continuous variable were analyzed by Student`s t-test and presented as mean +/- SD. Categorical data was cross tabulated by Chi – square test and presented as frequency and % at 95% CI (P≤ 0.05).Results: Vitamin B12 in control was 316.2±116.9 pg/ml and cases 270.5±131.1 pg/ml (P=0.023). Hypovitaminosis B12 (<300 pg/mL) was noted in 39% of control compared to 61% in GDM cases (P=0.0001). Vitamin B12 shows significant negative correlation with age (r= - 0.262, P=0.0001), gestational age (r= - 0.238, P=0.001), gravida (r= - 0.277, P=0.0001), FBG (r= - 0.284, P=0.0001) and RBG (r= - 0.229, P=0.0001). Vitamin B12 shows non – significant correlation with HbA1c (r= - 0.014, P=0.083). Conclusion: We found hypovitaminosis B12 in 61% of GDM cases. Vitamin B12 shows significant negative correlation with age, gestational age, gravida, fasting and random blood glucose.